Posttraumatic growth and postpartum depression in women after childbirth: The moderating role of postpartum negative life events. Issue 9 (16th June 2022) - Jiang, Cuiting; Zhuang, Youqing; Li, Zhiyun; Lin, Wenxuan; Huang, Pei; Feng, Yongshen; Liu, Shaofei; Zhang, Lifeng
Abstract: Aim: This study aimed to investigate the implications of postpartum negative life events on postpartum depression and posttraumatic growth in women after childbirth. Methods: A sample of 280 postpartum women at a level III hospital in China provided data on postpartum depression, negative life events, and posttraumatic growth with a cross‐sectional design. Results: The scores of both postpartum depression and negative life events exhibited a quadratic correlation with posttraumatic growth in women after childbirth, and negative life events significantly moderated the associations between depression and overall posttraumatic growth and its three dimensions: personal strength, spirit change, and relating to others. Conclusions: Women can experience positive psychological growth after childbirth, and this study provides new evidence of an interaction between postpartum depression and negative life events in the prediction of psychological growth, highlighting the moderating role of negative life events. This study could help direct mental health professionals to target interventions that provide more psychological support to reduce the impact of depression and negative life events, which will be conducive to improving women's psychological growth.